Survival Rate and Growth Length of Catfish (Clarias gariepinus) Exposed to Microplastics - Diana Permatasari; Mohamad Fadjar; Ating Yuniarti (Journal of Aquaculture and Fish Health, 2023)
Aquaculture has a land potential of 17.92 million ha consisting of 2.83 million ha of freshwater aquaculture potential, 2.96 million ha of brackish water aquaculture and 12.12 million ha of marine aquaculture. One of the freshwater species that has the potential to be cultivated is catfish (C. gariepinus). But now, as a result of the decline in the quality of the freshwater environment, catfish are prone to contamination by plastic waste. If microplastic particles have accumulated in large numbers in the fish's body, it can clog the fish's digestive tract and affect the growth of catfish which will affect the results of aquaculture production. The purpose of this study was to determine the survival rate or survival rate of catfish exposed to microplastics. The research design used in this study was a Completely Randomized Design (CRD) with 1 control variable, namely no mixing of microplastics in commercial feeds and 3 different doses of microplastics, namely A (5%), B (10%), C (15%) mixed with commercial feed, where each treatment was repeated 3 times. The results of the one way ANOVA analysis showed that the treatment of exposure to microplastics with different doses did not have a significant effect (P<0.05) on the survival rate and length growth of catfish. The survival rate ranges from 65- 100%. Survival values that were not significantly different could indicate that there was competition for space and dominance of larger fish in the aquarium which affected fish growth, feed utilization and fish survival. Meanwhile, the length growth value ranged from 21-28cm. The length growth value which was not significantly different could indicate that the dose of microplastic used in the study did not result in muscle and bone cell division which was the cause of the increase in body length of fish.